Determining The Physical Fitness And Strike Indicators Of Young Boxer Girls Through A Special Bag - Ziyodulla Shukhratillayevych Khadiyatullayev (Euro Asian Journal Publishing, 2024)
In this article, we will determine the special physical fitness, physical qualities, strength, speed, agility, flexibility, endurance, indicators of young girl boxers who are participating in the national boxing team of Uzbekistan.
Keywords: physical fitness; physical qualities; agility; strength